Efektivitas Penggunaan Media Quizlet dalam Meningkatkan Kosakata Bahasa Arab pada Siswa SMP Plus Alfatimah Bojonegoro - Muthoharoh, Imroatul; Abidin, Munirul (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2023)
This study aims to determine the effectiveness of the use of Quizlet media in increasing the Arabic vocabulary mastery of class VII students at SMP PLUS Alfatimah Bojonegoro. The research design used in this study was a quasi-experimental using a quantitative approach. The type of design used is a pre-test post-test with a non-equivalent control group design. The data collected in this study consisted of primary data, namely the results of student learning tests and supporting data in the form of observations and interviews with teachers and students. The research tool used in this research is a matter of pre-test and post-test. The results of this study gave homogeneous pre-test and post-test experimental class results, respectively, namely 50.23 and 78.18. While the pre-test and post-test homogeneous values of the control class were 50.23 and 58.41, respectively. The hypothesis test using the t-test formula obtained a tcount of 8.967 > ttable of 2.001 with a significance value (2-tailed) of 0.000 <0.05. This means that H0 is rejected and Ha is accepted, which means that the use of Quizlet media is effective in increasing Arabic vocabulary mastery in class VII SMP PLUS Alfatimah Bojonegoro.